(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article is devoted to the analysis of the poetics of the historical novel “Izgutty Batyr” by the representative of Kazakh literature in China Bayakhmet Zhumabayuly. The study examines the images and characters of all the characters found in the work, provides information about the life and work of the writer. The proximity of the novel’s content to historical reality is proved on the basis of historical sources. In accordance with the specifics and nature of the categories of time and space, the traditions and lifestyle of the people characteristic of the depicted era are described. The work reveals the moods and thoughts of all the people depicted in the novel. On the basis of the application of various methods and techniques of studying poetics, according to literary theory, the harmonious use of artistic means in the writer’s work is determined. The article shows that the author achieves the full realization of the idea by describing the era in which he lived. The relevance of the study and introduction into scientific circulation of works on the analysis of Kazakh literature abroad as a major and urgent problem is substantiated. The main value of the work in question is the depiction of historical figures. This article is the first scientific work on the work of the writer, ethnographer Bayakhmet Zhumabayuly. It comprehensively analyzes the novel “Izgutty Batyr”, which tells about the struggle of the Kazakhs of the Altai Mountains, belonging to the Qing Empire, during the thorough settlement in the period after the 1820s. The article also analyzes some aspects of the work that make an indelible aesthetic impression on readers.